MANUFACTURING COMPANY PERFORMANCE IN INDONESIA: THE ROLE OF ORGANIZATIONAL CULTURE AND KNOWLEDGE MANAGEMENT - Rika Dwi Ayu Parmitasari, Rusnawati, Rusdi R & Wahidah Abdullah (International Journal of Research Science and Management, 2020)
Firm performance is an essential element factor in shaping the competitiveness of a company to gain a competitive advantage in its industry. Firm performance is specifically affected those related to the company’s resources. Organizational culture and knowledge management are resources owned by companies to be able to compete in the industry. The study focuses on analyzing the effect of organizational culture and knowledge management on the performance of manufacturing companies in Indonesia. Data in this study is primary data and secondary data. The sample of study is 152 respondents. To test the data, this study used multiple regression analysis. The results show that company performance are influenced simultaneously by organizational culture and knowledge management. Partially, the results of the study indicate the role of knowledge management in company performance. However, organizational culture has no role in the performance of manufacturing companies in Indonesia.